CPTED-based analysis of factors influencing perceived safety in the street environment of Nagoya - Haoyuan Xiao; Yoshinori NATSUME (Environment and Social Psychology, 2025)
Grounded in Crime Prevention Through Environmental Design (CPTED) and informed by social‑psychological theory, this study examines how street‑environment features shape pedestrians’ perceived safety through normative cueing and perceived guardianship. We combined a field survey and spatial analysis to sample representative sites in the Shinsakae district (Nagoya), then conducted laboratory experiments comprising eye‑tracking, Semantic Differential (SD) ratings, and a virtual‑reality (VR) replication. Stimuli were 24 photographs (12 daytime, 12 nighttime). Fifty participants (architecture=20; non‑architecture=30) first viewed photographs while gaze behavior was recorded, followed by SD ratings on 22 bipolar adjective pairs; a subset of scenes was presented in VR. Areas of Interest (AOIs) were defined by seven CPTED‑related factors that also function as social signals: lighting and sightlines (normative clarity, reduced ambiguity), cleanliness vs. untidiness (injunctive norms), greenery (affect regulation), signage/graffiti and fly‑posting (disorder cues), and pedestrian/vehicle activity (perceived capable guardianship and social density). Eye‑tracking heat maps and scan paths showed consistent attention to lighting elements, moving vehicles, and salient signage; untidy cues captured attention in ways associated with lower safety ratings. SD results converged with the gaze patterns: lighting and cleanliness were the most influential positive contributors, whereas visible disorder reduced perceived safety; the VR condition approximated daytime judgments but not nighttime. Taken together, the findings suggest that physical design acts partly by shaping normative expectations and perceived guardianship—pointing to interventions that pair maintenance and lighting with place management to strengthen collective efficacy and the salience of prosocial norms.